2016
DOI: 10.1002/ajcp.12026
|View full text |Cite
|
Sign up to set email alerts
|

Thriving Among African‐American Adolescents: Religiosity, Religious Support, and Communalism

Abstract: While research has identified some positive factors in the lives of African-American adolescents, there is limited, yet growing, empirical research examining how positive factors foster thriving for these youth. Using a positive youth development framework, we examined naturally occurring factors that promote thriving among African-American adolescents. This cross-sectional study included 152 youth who were surveyed at five Black churches in a large Midwestern city. Using MPlus, the structural regression model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 63 publications
0
31
1
Order By: Relevance
“…Spencer, Dupree, Swanson, and Cunningham (1996) found that religious engagement and attendant factors were significant supports for the ethnic identity and self-efficacy processes of African American girls. Results from Gooden and McMahon (2016) suggest that religiosity, religious social support, and communalism were significantly associated with thriving outcomes for African American adolescents in predominantly Black churches. Similarly, Brown (2008) found positive associations between the resilience of African American undergraduates who reported receiving positive racial socialization messages and perceiving social support.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Spencer, Dupree, Swanson, and Cunningham (1996) found that religious engagement and attendant factors were significant supports for the ethnic identity and self-efficacy processes of African American girls. Results from Gooden and McMahon (2016) suggest that religiosity, religious social support, and communalism were significantly associated with thriving outcomes for African American adolescents in predominantly Black churches. Similarly, Brown (2008) found positive associations between the resilience of African American undergraduates who reported receiving positive racial socialization messages and perceiving social support.…”
Section: Discussionmentioning
confidence: 95%
“…Religious engagement may provide these adolescent with access to religious social support and its attendant benefits. For example, African American adolescents attending predominantly Black churches who reported greater religious social support tended to have higher levels of thriving (Gooden & McMahon, 2016).…”
Section: Black Adolescents and Religious Social Supportmentioning
confidence: 99%
“…Religiosity and spirituality also support meaning-making, a sense of purpose, effective coping, resilience, and the development of a range of virtues, including humility, compassion, forgiveness, optimism, and prosociality (Gooden and McMahon 2016;Mattis 2002;Mattis et al 2000Mattis et al , 2003Mattis et al , 2017Utsey et al 2007;Yeh et al 2011). However, the mechanisms and processes by which religiosity and spirituality influence positive development for Black children, youth, and adults who reside in urban settings, in particular, remain understudied.…”
Section: Urban Contexts As a Unique Developmental Nichesmentioning
confidence: 99%
“…Several factors influence adolescent sexual initiation; one such factor is religiosity. Given that black adolescents are among the most religiously active adolescents in the USA (Gooden and McMahon 2016; Smith 2003), this study seeks to examine the associations between religious socialization, religiosity, and sexual initiation among a nationally representative sample of black adolescents.…”
Section: Introductionmentioning
confidence: 99%